STRATEGY FOR INCREASING PROFITS OF PANIN DUBAI SHARIA BANK IN 2021-2023 - Syamsiyah, Nur; Ikit (Journal Of Islamic Ekonomic and Business, 2024)
To maintain stable income or profits, banks need to set strategies to increase net profits every year.The bank will continue to utilize sharia banking services in line with its efforts to further improve and continue to offer attractive products to the public.Descriptive qualitative is a research method that describes data systematically, factually and accurately by exploring deeper depth or meaning. This research aims to observe the strategies that have been implemented by Panin Dubai Syariah bank in its implementation to generate profits for the Company, and find new strategies that can increase and stabilize profits in the future.